The taxonomy and biogeography of Cuban Ophioninae (Hymenoptera: Ichneumonidae) - Fernández-Triana, José L. (Zootaxa, 2005)
A comprehensive study of Cuban Ophioninae (Hymenoptera: Ichneumonidae) was carried out. Nine new species are described: Ophion picocuba sp. nov., Thyreodon alayoi sp. nov., Thyreodon gabrieli sp. nov Enicospilus cheoi sp. nov., E. iangauldi sp. nov., E. grilloi sp. nov., E. hansonorum sp. nov., E. teremariae sp. nov. and E. wahli sp. nov. Five species are recorded for the first time to the island: Enicospilus dispilus, E. gallegosi, E. neotropicus, E. sondrae and E. woldai. Thyreodon sp. (Alayo, 1973) is T. fulvescens Cresson. New biological information regarding host records is provided for E. flavus and O. flavidus. A preliminary analysis of distribution of ophionines within the Cuban archipelago and their relationships with the Caribbean, Florida (USA) and Central American faunas are also discussed.KEY WORDS: Ophioninae, taxonomy, Biogeography, CubaSe revisa la subfamilia Ophioninae (Hymenoptera: Ichneumonidae) en Cuba. Se describen nueve especies: Ophion picocuba sp. nov., Thyreodon alayoi sp. nov., Thyreodon gabrieli sp. nov., Enicospilus cheoi sp. nov., E. iangauldi sp. nov., E. grilloi sp. nov., E. hansoni sp. nov., E. teremariae sp. nov. y E. wahli sp. nov. Cinco especies se registran por primera vez para el país: Enicospilus dispilus (Szépligeti), E. gallegosi Gauld, E. neotropicus Hooker, E. sondrae Gauld y E. woldai Gauld. Thyreodon sp. (Alayo, 1973) es T. fulvescens Cresson. Se aporta nueva información biológica en relación con registros de hospederos para E. flavus y O. flavidus. Se analiza preliminarmente la distribución de la subfamilia en el archipiélago cubano y sus relaciones con el Caribe insular, Florida (USA) y América Central.PALABRAS CLAVE: Ophioninae, taxonomía, Biogeografía, Cuba